(untitled) (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2025)
Experiences in toxic relationships often trigger significant emotional stress and impact mental health disorders. This study aims to develop a web-based expert system using the Case-Based Reasoning (CBR) method to evaluate anxiety levels caused by toxic relationships. The system is designed to provide more specific treatment by accurately analysing patterns of disorders resulting from toxic relationships. The system’s development follows the waterfall model. System testing was conducted using the black-box testing method, demonstrating that the system performs as expected. The results of manual calculations were compared with the system outputs and showed consistency. Testing using 300 cases—80% as training data (240 cases) and 20% as testing data (60 cases)—achieved an accuracy of 91.67%. The recommendations provided include initial steps to manage anxiety. This indicates that the CBR method effectively distinguishes anxiety levels based on similar cases. These findings contribute to clinical psychology by providing a technological tool for quickly identifying anxiety levels. For practitioners, this system can serve as an initial reference before further treatment, while for users, it offers easy access to understanding their mental condition. This system is expected to be an innovative solution supporting accessible mental health care.